Physiology of Erwinia mallotivora-infected papaya seedlings (Carica papaya L.) Treated with silicon - Yamanludin, Noor Shahida (2015)
Papaya dieback disease caused by Erwinia mallotivora has been a threat to the Malaysia‟s papaya industry destroying more than one million plants and chemical control of the disease is almost impossible. Based on the available information on the possible beneficial effects of silicon (Si) in increasing crop resistant to bacterial diseases in plants, this study was designed. This study was conducted with the intention to characterize the development of dieback disease on papaya seedlings, to investigate the effects of varying concentrations of Si on dieback disease development, physiological and biochemical aspects of E. mallotivora infected papaya seedlings as well as to elucidate the possible mechanisms of Si in mediating the beneficial effects in reducing the occurrence of dieback disease in papaya seedlings. Two cultivars of papaya were used in the first and second experiments which were papaya cultivar Eksotika and papaya cultivar Eksotika II. Only papaya cultivar Eksotika II was used in the third experiment. In the first experiment, eight week old plants inoculated with E. mallotivora suspension (1 x 108 CFU/ml) showed a dieback disease symptoms started from day 3 after inoculation (DAI) with small water soaked lesion at point of inoculation (3 cm in length) and the size of lesion has increased with time. Dieback of shoot occurred at 9 DAI and the plant was fully wilted and dead at 11 DAI. Besides visual symptoms appearance of dieback disease, infection with bacteria E. mallotivora had also caused biochemical changes in papaya Eksotika and Eksotika II in the second experiment. Leaf of Eksotika II had higher content of total sugar, total protein, peroxidase activity and polyphenol oxidase activity compared to papaya Eksotika. In stem, papaya Eksotika II had higher total phenol and total protein compared to papaya Eksotika. Higher total protein, peroxidase activity and polyphenol oxidase activity were found in roots of papaya Eksotika II compared to papaya Eksotika. Papaya Eksotika II had higher photosynthetic rate compared to papaya Eksotika. However, stomata conductance was found higher in papaya Eksotika compared to papaya Eksotika II. There was no significant different in transpiration rate for both papaya cultivars. Studies on photosynthetic activity of both papaya cultivars showed that non-infected plant had higher photosynthetic rate, stomatal conductance and transpiration rate compared to inoculated plant. To elucidate the effects of Si in regulating dieback disease in the third experiment, two-week old papaya seedlings were sprayed with 50 ml of sodium silicate (28.5 % SiO2, 8.5% Na2O) at four level of SiO2 (0, 50, 100, 150 mg/L), at a weekly interval for 8 weeks. Results showed lesion length and disease symptom were reduced when treated with Si. At 100 mg/L Si level, highest content of total sugar, total phenol, total protein, peroxidase activity, polyphenol oxidase activity, photosynthesis, transpiration rate and stomatal conductance were recorded. Si content in plant tissues increased markedly with increasing Si level in the applied solution of 0 mg/L (control), 50 mg/L, 100 mg/L and 150 mg/L, with their respective concentrations (0.120 mg/g DW, 0.164 mg/g DW, 0.246 mg/g DW and 0.218 mg/g DW). In conclusion, papaya dieback disease symptoms for papaya cultivar Eksotika and Eksotika II occurred as early as day 3 after inoculation with bacteria E. mallotivora. Infection with E. mallotivora caused certain biochemical and physiological changes in papaya plants. Si applied as sodium silicate had shown positive effects on papaya plant infected with dieback disease caused by bacteria E. mallotivora. Si at 100 mg/L showed positive effects in reducing dieback disease caused by the bacteria E. mallotivora. However, treatment with sodium silicate did not prevent plants from dying. Papaya seedlings were dead at 18 days after inoculation with bacteria E. mallotivora. Results showed that sodium silicate at concentration of 100 mg/L and 150 mg/L SiO2 were able to slow down the outbreak of dieback disease development but failed to stop dieback disease development and results in death of papaya plants.